Pengaruh Integrasi Fintech dan Pembiayaan Mikro Syariah Terhadap Pertumbuhan UMKM di Ekosistem Pariwisata Halal di Lombok - Aolia, Jumatul; Safina, Safina; Nur’aini, Nur’aini (Lembaga Pengembangan Kinerja Dosen, 2025)
The integration of financial technology (fintech) and Islamic microfinance represents a strategic innovation in strengthening financial access and supporting the growth of MSMEs, particularly within the halal tourism ecosystem. This study aims to quantitatively analyze and examine the influence of fintech and Islamic microfinance integration on the growth of MSMEs in the context of halal tourism in Lombok. The main focus is to assess the extent to which the collaboration between technology-based financial services and Sharia-compliant financing systems can enhance access to capital, operational efficiency, and business development capacity among MSME actors. This research employs a quantitative approach with an associative research type. Data were collected through Likert-scale questionnaires distributed to UMKM actors in Sembalun Village, East Lombok, a prominent halal tourism destination in Indonesia. Respondents were selected using purposive sampling based on specific criteria. Each research variable was measured using five relevant indicators. Multiple linear regression analysis was applied with the assistance of SPSS version 22 to test the hypotheses. The results indicate that both fintech integration and Islamic microfinance have a significant influence both partially and simultaneously on UMKM growth. These findings offer valuable insights for policy formulation and strategic efforts to empower UMKM in an innovative and sustainable manner, thereby contributing to local economic development based on halal tourism.